Peningkatan Literasi Energi Ibu Rumah Tangga melalui Pelatihan Aplikasi Simulasi Listrik Berbasis Web - Silitonga, Riana Magdalena; Kristiana, Stefani Prima Dias; Silalahi, Agustinus; Lembana, Devi Angrahini Anni; Budiyanta, Nova Eka (Jurnal Pengabdian UNDIKMA, 2026)
This community service program aims to enhance participants’ knowledge and promote more energy-efficient electricity consumption practices among members of the Family Welfare Empowerment (PKK) group through training on the use of a web-based electricity consumption simulation application. The program was implemented through educational sessions, hands-on training, simulation exercises, and mentoring involving 35 PKK members in Sampora Village, Tangerang Regency. Program effectiveness was evaluated using pre-test and post-test assessments, direct observations, and participant satisfaction questionnaires. The data were analyzed descriptively. The results showed a significant improvement in participants’ knowledge, with the mean score increasing from 56.8 before the training to 85.2 after the training, representing an increase of 28.4%. In addition, 91% of participants reported that the application was easy to use, 94% considered the training materials clear and easy to understand, and 89% expressed their willingness to adopt energy-saving practices in their daily household activities. Overall, the program successfully improved participants’ energy literacy and basic digital competencies while equipping them with practical skills to estimate household electricity consumption, enabling them to make more informed decisions to reduce energy use and lower monthly electricity costs.